Avaliação das atividades antimicrobiana, leishmanicida e citotóxica dos fungos endofíticos Diaporthe sp. E Pseudofusicoccum sp. obtidos de mangue e cerrado brasileiros - Moreira, Carla Cristina (Universidade Federal de São Carlos, 2020)
The mangrove is a transition ecosystem between the terrestrial and the marine environment, typical of tropical and subtropical regions. The Brazilian savannah is an ecosystem that is mainly characterized by the savanna biome, which are transition zones between meadows and forests and are native to tropical regions of the dry season. In these two systems, several microorganisms have already been isolated, including endophytic fungi, capable of producing substances with antimicrobial and leishmanicidal activities, among others. Based on this information, this study aimed to evaluate the biotechnological potential of crude extracts (EB) obtained from endophytic fungi Diaporthe sp. and Pseudofusicoccum sp., isolated from Brazilian mangroves and savannah, respectively. In vitro antimicrobial tests with human pathogens, leishmanicidal tests and cytotoxic tests were performed. In antimicrobial assays, the minimum inhibitory concentration of 50% (MIC50) between 756 µg.mL-1 and 949 µg.mL-1 and the minimum inhibitory concentration of 90% (MIC90) between 3.940 and 3.980 µg.mL-1 were found for the EB of the mangrove isolate. For EB isolated from the savannah, CIM50 between 4.228 µg.mL-1 and 29.630 µg.mL-1 and CIM90 between 9.24 µg.mL-1 and 38.250 µg.mL-1 were found. The Minimum Bactericidal Concentration (CBM) was found for the microorganism Bacillus subtillis, at a concentration of 10.000 µg.mL-1. In leishmanicidal assays, the results show cell death of 90% at concentrations of 6.000 and 10.000 µg.mL-1 and 80% at a concentration of 4,000 µg.mL-1 for the EB of the mangrove isolate. In the EB of the savannah isolate, the leishmanicidal assays showed cell viability above 90% at concentrations of 20.000 and 40.000 µg.mL-1. For cytotoxicity tests on the EB of the mangrove isolate, cell viability between 55 and 73% was presented. For the savannah isolate, cell viability between 5.41 to 16.84% was presented. These results reinforce the biotechnological potential of microorganisms isolated from mangroves and savannah, represented by the isolates tested in this work.
Evaluation of antimicrobial, leishmanicidal and cytotoxic activities of endophytic fungi Diaporthe sp. and Pseudofusicoccum sp. obtained from Brazilian mangroves and cerrado
Keywords: Mangue; Cerrado; Fungos endofíticos; Ensaios antimicrobianos; Ensaios leishmanicidas; Mangrove; Savannah; Endophytic fungi; Antimicrobial assays; Leishmanicidal assays; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA